Neonatal sepsis in a tertiary care hospital in Delhi, India: study of microbial profile and antimicrobial susceptibility pattern - Gupta, Sangita; Singh, Varun Kumar; Singhal, Sanjay; Chowdhary, Priti (International Journal of Contemporary Pediatrics, 2019)
Background: Sepsis is one of the most common cause of neonatal deaths globally more so in low and middle-income countries. The key to management is high degree of clinical suspicion and prompt initiation of empirical antibiotic therapy pending investigations’ results. Knowledge of one’s own NICU flora and antimicrobial susceptibility pattern guides in choosing correct antibiotic therapy to pediatrician. If this data is standard and comparable across different sites, then it also helps in formulating regional and National treatment guidelines. Present study was therefore undertaken to study microbial flora of present NICU and analyze their antimicrobial susceptibility pattern and formulate antimicrobial policy. Methods: Data of blood culture isolates sent from suspected cases of neonatal sepsis received from January 2017 to July 2018 was analysed by “WHONET”. Results: One hundred ninety-three non-repeat isolates were obtained from 992 blood culture samples. Coagulase negative Staphylococcus and K. pneumoniae were the most common isolates. Non albicans Candida were responsible for majority of fungal infection. There was an outbreak of C. pelliculosa for six months. Most of the bacteria were multidrug resistant (MDR). However, except one all other Candida isolates were sensitive to antifungal drugs. Conclusions: WHO guidelines suggest use of penicillin and gentamicin for neonatal sepsis. But in present study, they were not found useful, instead amikacin, netilmicin and piperacillin-tazobactam were found useful and changes were made in antibiotic policy. Authors therefore recommend regular monitoring of antimicrobial susceptibility pattern followed by necessary changes in antibiotic policy for reasonable empirical therapy.